2013
DOI: 10.1002/chem.201301071
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Functions of Hybrid Membranes with Rings of Ag NPs Anchored at the Edges of Highly Ordered Honeycomb‐Patterned Pores

Abstract: We report a new, simple strategy to apply honeycomb films for the patterning of colloidal particles. By combination of a "bottom-up" breath figure method and the electrochemical properties of the honeycomb films of ferrocenyl-based oligomers, highly ordered hybrid membranes coated with ring-like patterning of 0D- and 1D-Ag nanoparticles (NPs) have been fabricated. One interesting phenomenon is that the nucleation and adsorption of Ag dots occurred preferentially at the edges of the micropores. The hybrid membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…After running CV in an aqueous solution containing 0.1 mol L −1 KNO 3 and 0.5 mmol L −1 HAuCl 4 for 800 s, it was found that Au nanoclusters had been successfully deposited in the pores (Figure D). Compared to similar studies reported previously, the deposition of Au nanoclusters demonstrated here is better, that is, they were found to only reside inside the pores. This improvement could be ascribed to the better electrochemical responsiveness of the honeycomb film, which is consistent with our discussions mentioned above.…”
Section: Resultscontrasting
confidence: 69%
See 2 more Smart Citations
“…After running CV in an aqueous solution containing 0.1 mol L −1 KNO 3 and 0.5 mmol L −1 HAuCl 4 for 800 s, it was found that Au nanoclusters had been successfully deposited in the pores (Figure D). Compared to similar studies reported previously, the deposition of Au nanoclusters demonstrated here is better, that is, they were found to only reside inside the pores. This improvement could be ascribed to the better electrochemical responsiveness of the honeycomb film, which is consistent with our discussions mentioned above.…”
Section: Resultscontrasting
confidence: 69%
“…[4] The preparationo fh oneycombs tructures has been expanded from solid substrates to the air/waterinterface and the templates have been extended from droplets of watert ot hose formed by nonaqueous solvents or microemulsions.I nfluences of various factors on the morphology of the honeycombs tructures, such as humidity,g as flow,t emperature, concentration of the materials, type of substrate, and organic solvent,h ave been fully investigated. Up to now,v arious candidates have been explored to form honeycomb structures.B esides polymers with diversec ompositions and structures, [12][13][14][15] av ariety of materials with attractive properties have also been tried, including carbon nanotubes( CNTs), [16,17] grapheneo xide (GO), [18] proteins, [19] small organic molecules, [20][21][22] and inorganic-organic hybrids. [10,11] Ab ig advantage of the honeycombs tructures fabricated by the BF methodi st hat the functions of the films can be facilely tuned by engineeringt he starting materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the main approaches for the metal modifications of honeycomb films are performed after the BF process [12,13]. Some techniques have been developed for the metal modification of honeycomb films, such as chemical deposition [14], electrodeposition [11,15], electroless plating [16,17], vapor deposition [18], and physical adsorption [19]. Although these techniques were successfully applied in the fabrication of metallized honeycomb films, they involve elaborate procedures, post-modifications, and/or sophisticated instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…Honeycomb‐patterned porous films have attracted tremendous interest owing to their wide applications in sensors, catalysts, electronic devices, biology, membrane separation, and so on. The breath figure (BF) method, firstly reported by Francois and co‐workers is a facile and versatile approach to fabricate such structures.…”
Section: Introductionmentioning
confidence: 99%